The Role of Candida Infection in Pathological Processes in the Body (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Candidiasis is a mycotic infection caused by yeast-like fungi of the genus Candida. The genus Candida belongs to the domain (superkingdom Supraregnum) Eukaryota, the kingdom (Regnum) Fungi, the division (Phylum) Ascomycota, the subdivision (Sub-Phylum) Ascomycotina, the class (Classis) Saccharomycetes, the subclass (Subclassis) Ascomycetidae, the order (Ordo) Saccharomycetales, the family (Family) Saccharomycetaceae, and the genus (Genus) Candida.